Integrated Forest Biorefinery Applied to a CTMP Process: Pre-Extraction of Acetic Acid - He, Chengda; Yuan, Zhirun; Mao, Changbin; Ni, Yonghao (Current Organic Chemistry, 2013)
Acetic acid is one of the promising bio-products following the Value Prior to Pulping (VPP) concept, which is one of the options for Integrated Forest Biorefinery. In a typical chemi-thermo-mechanical pulping (CTMP) process, the chemical pre-treatment may be retrofitted into the pre-extraction stage. The potential of pre-extraction of acetic acid under the conditions similar to a CTMP process was evaluated in this study. The pre-extraction yield of acetic acid increased with the increase of cooking time and temperature. The maximum acetic acid yield was 31.25% at 150°C and 60 min after the cooking in an M/K digester. The pre-extraction yield increased to 42.05% after the cooked chips were broken down into pulp fibers, indicating that some of the released acetic acid was trapped inside the wood chips and a post-mechanical treatment could enhance the diffusion of acetic acid to the liquid phase.
Keywords: Pre-extraction